Adjustment to Higher Education: A Comparison of Students With and Without Disabilities - Lipka, Orly; Sarid, Miriam; Aharoni Zorach, Inbar; Bufman, Adi; Hagag, Adi Anna; Peretz, Hila (Frontiers in Psychology, 2020)
The present study examined adjustment to higher education among students with disabilities immediately following their first year of study and onwards, with three primary objectives. First, we examined whether students with no disabilities adjust better to higher education than students with disabilities (mental health, physical, sensory, ADHD/LD). Second, we examined differences among the specific disability groups in adjustment to higher education overall and in specific subscales. Finally, we examined the unique pattern of adjustment in each disability group, and sought to determine whether the groups differed with respect to this pattern. Of the 469 students who participated in the study, 234 had disabilities (mental health, sensory, ADHD/LD, physical) and 235 were matched controls. The results indicated that students with disabilities as a whole reported lower adjustment than did controls. A close examination of the differences between the disability groups on the four subscales demonstrated unique adjustment challenges for each of the groups. The findings demonstrate the importance of specifically examining each disability group, to learn about needs and support.